Response of Flood Events to Land Use and Climate Change Analyzed by Hydrological and Statistical Modeling in Barcelonnette, France - Ramesh, Azadeh; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book is an original and novel contribution to flood hazard assessment, climate change and land use change and is intended to serve both as an effective source of information and a valuable basis for priority setting and further technical, financial and political decisions regarding flood hazard assessment. The study area is located on the floodplain of the Ubaye River in the Barcelonnette area, part of the Alpes de Haute Provence in southeast France. The book offers a comparative overview of the major challenges faced when dealing with flood hazards. The research presented is intended to promote a deeper understanding of how climate change and land use change processes have evolved from past to present, and how they affect the flow regime of the Ubaye River based on sound and reproducible scientific arguments. The methodology implemented ranges from remote sensing interpretation to hydrodynamic modeling and includes the application of spatial and statistical modeling. The results of this research provide essential information for policymaking, decision-making support and flood hazard planning in the Barcelonnette area.
Theoretical background -- Methodology -- Study area -- Available data -- Results -- Overall conclusion -- Discussion.
Keywords: Geography; Hydraulic engineering; Remote sensing; Geology; Physical geography; Climatic changes; Geography; Physical Geography; Climate Change; Natural Hazards; Hydrogeology; Remote Sensing/Photogrammetry.